Effect of Urinary Tract Infection on Premature Birth: A Meta Analysis - Palupi, Raras Indung; Widyaningsih, Vitri; Murti, Bhisma (Journal of Maternal and Child Health, 2022)
Background: Neonatal mortality in the world is mostly caused by premature birth (43%), and in Indonesia the biggest cause of neonatal death is premature birth (45%). One of the causes of pregnant women experiencing premature labor, namely urinary tract infections due to changes in the urinary tract system during pregnancy. This study aims to analyze the primary study of the effect of urinary tract infections in pregnant women on preterm delivery with a meta-analysis. Subjects and Method: This study is a meta-analysis with the following PICO, population: pregnant women. Intervention: Having a urinary tract infection. Comparison: No urinary tract infection. Outcome: Premature delivery. The articles used in this study were obtained from three databases, namely Google Scholar, Pubmed, and Science Direct. Keywords to search for articles (“urinary tract infection” AND “preterm labor” OR “premature birth” OR “premature labor”). The included article is full text in English with a case-control study design from 2006 to 2022 and reports the adjusted odds ratio in a multivariate analysis. The selection of articles is done by using PRISMA flow diagram. Articles were analyzed using the Review Manager 5.3 aplikasi application. Results: A total of 10 case-control studies from Iran, Iraq, India, Tanzania, Ethiopia, and Peru were selected for the meta-analysis. The data collected showed that pregnant women with urinary tract infections increased the occurrence of preterm labor by 2.19 times compared to pregnant women who did not experience urinary tract infections (aOR= 2.19; 95% CI= 1.80 to 2.66; p<0.001). Conclusion: Urinary tract infection during pregnancy increases the incidence of preterm labor. Keywords: urinary tract infection, premature delivery, meta-analysis. Correspondence: Raras Indung Palupi. Master’s Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: Palupiraras05@gmail.com. Mobile: +6285337540058.